What are the economic and poverty implications for Sudan if the conflict continues through 2025? - Ahmed, Mosab O. M.; Raouf, Mariam; Siddig, Khalid (Informa UK Limited, 2026)
The ongoing conflict in Sudan, which began in April 2023, has triggered severe economic contractions, exacerbating poverty and unemployment while disrupting key sectors of the economy. This study employs an updated economywide database to assess the economic impact of a continued conflict through the end of 2025 under two scenarios of extreme and moderate contractions in the overall GDP. Our findings indicate that by the end of 2025, Sudan’s GDP would decline by 42% under the extreme scenario and 32% under the moderate scenario. The agrifood system would be particularly affected, with its GDP contracting by 33.6% and employment halving under the extreme scenario. Household incomes decline across all quintiles, with rural populations and women experiencing the sharpest losses. The national poverty rate is projected to rise by 19 percentage points under the extreme scenario, further deepening socioeconomic vulnerabilities. To mitigate the widespread adverse impacts of the conflict on the Sudanese economy, policies and interventions should prioritize the restoration of economic productivity, support the agrifood system and employment recovery strategies, and ensure that social protection measures are accessible to all households facing increased deprivation.